Magnesium Lithospermate B Protects Cardiomyocytes from Ischemic Injury Via Inhibition of TAB1–p38 Apoptosis Signaling - Du, Chang-Sheng; Yang, Rui-Fang; Song, Shu-Wei; Wang, Yi-Ping; Kang, Jiu-Hong; Zhang, Ru; Su, Ding-Feng; Xie, Xin (Frontiers in Pharmacology, 2010)
Danshen has been used in traditional Chinese medicine (TCM) for hundreds of years to treat cardiovascular diseases. However, its precise cardioprotective components and the underlying mechanism are still unclear. In the present study, we demonstrated that in a rat model of acute myocardial infarction, the treatment with magnesium lithospermate B (MLB), the representative component of phenolic acids in Danshen, significantly reduced the infarct size and the blood lactate dehydrogenase level. In contrast, tanshinone IIA, the representative component of lipophilic tanshinones in Danshen, had no such protective effects. Moreover, in the simulated ischemia cell model, MLB treatment considerably increased the cell viability and reduced the sub-G1 population and the apoptotic nuclei, indicating its anti-apoptotic effect. Further mechanism study revealed that the ischemia induced p38 phosphorylation was abolished by MLB treatment. Interestingly, MLB specifically inhibited the TGFβ-activated protein kinase 1-binding protein 1 (TAB1) mediated p38 phosphorylation through disrupting the interaction between TAB1 and p38, but it did not affect the mitogen-activated protein kinase 3/6 mediated p38 phosphorylation. In conclusion, the present study identifies MLB as an active component of Danshen in protecting cardiomyocytes from ischemic injury through specific inhibition of TAB1-p38 apoptosis signaling. These results indicate TAB1-p38 interaction as a putative drug target in treating ischemic heart diseases.